PHENOMENOLOGY STUDY THE EXPERIENCE OF PERSONS WITH DIABETES MELLITUS WHO HAD EXPERIENCED OF HYPOGLYCEMIA EPISODES IN DEPOK CITY - Jon Hafan Sutawardana; Yulia; Agung Waluyo (NurseLine Journal, 2016)
Hypoglycemia is an acute complication of diabetes mellitus which frequently occur repeatedly identified by blood glucose level less than 70 mg/dl. Diabetic patients experience dilemmatic situation where they are required to obtain diabetes drug therapy tocontrol blood sugar level remain normal, but facing another concerns about the side effects of treatment which can lead to complication of hypoglycemia. This condition will affect the psychological fearness of repeated attacks that result a traumatic feelings in diabetic patients. The study aimed to gain in depth understanding of diabetic patients experiences who had experienced of hypoglycemia episodes in Persadia Depok. This was a qualitative research which applied phenomenology method and involved six participants with diabetes mellitus experienced hypoglycemia episodes. Data were collected using in-dept hinterview and field notes. A Colaizzi's content analysis method was operated across data andrevealed 6 themes: decline in physical function while in response to hypoglycemia, traumatic feelings when experiencing hypoglycemia, participants' understanding that caused of hypoglycemia, awareness of hypoglycemia prevention, internal beliefs became the main source of coping strategy to face hypoglycemia and nursing care needs. The results of this study suggested a need of improvement innursing education for patients with hypoglycemia.